Genetic Algorithm optimized Neural Network based Adaptive ECG Interference Canceller for Premature Infants in Incubators - Mahil J; T. Sree Renga Raja (Institute of Advanced Engineering and Science, 2013)
This paper proposed a hybrid neural network Back propagation (BP) algorithm optimized by Genetic Algorithm (GA) for the diminution of the fundamental electromagnetic interferences in Incubators. Gradient based techniques have been proposed in the past for the elimination of incubator noise but they are susceptible to local minima problem. Genetic algorithms are a class of optimization procedure which is good at examining an intelligent way for selecting the number of hidden layer neurons, learning rate and momentum constant of the Artificial Neural Network (ANN) to find values close to the global minimum. The result analysis shows that the proposed approach shows good performance in cancelling the ECG interference over other conventional approaches.DOI: http://dx.doi.org/10.11591/ij-ai.v2i4.2293